Evaluating Samarinda City's Sub-district Digitalization Policy for Enhanced Public Services - Hidayatullah, Aji Syarif (Indonesian Journal of Public Policy Review, 2024)
General Background: The rapid advancement of digital technology has significantly impacted public service delivery, with governments worldwide exploring digital transformation to enhance administrative efficiency and public engagement. Specific Background: In Samarinda City, the implementation of a digitalization trial program in sub-districts has been undertaken to address the existing dissatisfaction among the public with conventional public services. Knowledge Gap: While digitalization is presumed to improve service efficiency and accessibility, empirical evidence on its effectiveness, particularly at the sub-district level, remains sparse. Aims: This study aims to evaluate the policy of the digitalization trial program in Samarinda City's sub-districts, focusing on its capacity to improve service quality and its broader impacts on public administration. Results: The findings reveal significant enhancements in service efficiency and user satisfaction, marked by a decrease in physical visits to sub-district offices as residents increasingly access services online. Novelty: This research contributes to the understanding of digital transformation at a micro-administrative level, a less explored area in digital governance studies. Implications: The successful implementation of the digitalization program in Samarinda City suggests potential scalability to other regions, highlighting the importance of strategic planning and continuous training to realize the benefits of digital governance fully. Highlights: Efficiency Gains: Reduced physical visits signify increased service efficiency. User Satisfaction: Digital services improved accessibility and speed, enhancing satisfaction. Scalability: The program's success highlights its potential for broader application, requiring strategic planning and continuous training. Keywords: E-Government, Digitalization Program Policy, Community Services